Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1999
DOI: 10.1115/99-gt-259
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Unsteady Heat Transfer in a Transonic Film Cooled Turbine Cascade

Abstract: This paper reports on an investigation of the heat transfer on the suction side of a transonic film cooled turbine rotor blade in a linear cascade. Heat transfer coefficient and film effectiveness are first determined for steady conditions. The unsteady effects of a passing shock on the heat transfer are then investigated. The film cooling pattern used is a showerhead design with three rows on the suction side, one row at the stagnation point and two rows on the pressure side. The experiments were performed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Dunn et al [10], followed by Abhari et al [11], have performed time-averaged and time-resolved measurements of a transonic single-stage research turbine in a short duration facility. More recently, Popp et al [12] and Nix et al [13,14] reported the progression effect of shock waves on film-cooled blades through a transonic turbine linear cascade.…”
mentioning
confidence: 99%
“…Dunn et al [10], followed by Abhari et al [11], have performed time-averaged and time-resolved measurements of a transonic single-stage research turbine in a short duration facility. More recently, Popp et al [12] and Nix et al [13,14] reported the progression effect of shock waves on film-cooled blades through a transonic turbine linear cascade.…”
mentioning
confidence: 99%
“…Thus, it is often advantageous to examine a given film-cooling scheme by analyzing its convective heat flux, q, governed by q = -T") (1) where h is the convective heat-transfer coefficient, Taw is the adiabatic wall temperature, and T" is the temperature of the wall. (2) where Tr is the recovery temperature. If this were the only parameter to vary in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Film cooling is known to increase mixing, which in turn increases h [1]. Popp et al [2] showed that, for no fibn cooling present, Eq. (1), the heat flux to the wall would increase with film cooling, causing an undesired effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations